Application of Sumudu decomposition method to solve nonlinear system Volterra integrodifferential equations - Eltayeb, Hassan; Kilicman, Adem; Mesloub, Said (Hindawi Publishing Corporation, 2014)
We develop a method to obtain approximate solutions for nonlinear systems of Volterra integrodifferential equations with the help of Sumudu decomposition method (SDM). The technique is based on the application of Sumudu transform to nonlinear coupled Volterra integrodifferential equations. The nonlinear term can easily be handled with the help of Adomian polynomials. We illustrate this technique with the help of three examples and results of the present technique have close agreement with approximate solutions which were obtained with the help of Adomian decomposition method (ADM).